A rebellious thinker or a cultural icon: Chan master Huineng in theatrical resemiotization. (May 2023) - Yu, Hailing
Adopting a multimodal social semiotic approach, this study investigates the resemiotization of the story of Huineng in two theatrical performances, the opera Snow in August performed in Taipei in 2002, and the musical theater The Sixth Patriarch Huineng performed in Shanghai in 2007. Although both claim to have been based on the historical record of Huineng, especially the Platform Sutra, significant differences exist. Focusing on the differences, the study investigates: (1) how semiotic resources of language, music and mise-en-scène are adopted to present Huineng in a particular way; and (2) why the semiotic resources are mobilized to present Huineng in such ways. Analysis shows that while Snow in August presents Huineng as a rebellious, independent thinker through episodes concerning Huineng's innate enlightenment, breaking the alms-bowl and burning the robe, and his decline of the imperial invitation, The Sixth Patriarch Huineng presents Huineng as a cultural icon by emphasizing his reconciliation with former enemy Shenxiu, and the harmonious relationship between Huineng and the other characters. Each performance is contextualized to reveal ways in which resemiotization is socially situated and ideologically positioned.